Intensity; in-ten-si-ty; noun. 1. Often used ambiguously within resistance training. 2. Is it time to drop the term altogether? - Steele, J. (British Journal of Sports Medicine, 2014)
Recently in BJSM, Dr Berkoff highlighted some `hot topics` in sports and exercise medicine. A variety of topics were covered, all of which were `hot`. Of particular interest, however, was the fact that Dr Berkoff preceded his article with a definition of `hot`. Within sports and exercise medicine, and indeed in all scientific disciplines, definitions are of great importance. In fact, "The primary advantage of operational definitions lies in the unification of science and the resolution of controversy." It is the definition and use of a term within a topic that might also be deemed as `hot` that this editorial attempts to address: Intensity in resistance training (RT). Recent publications regarding RT have attempted to offer clarification on the definition of intensity. Fisher and Smith wrote regarding the use of the term intensity within RT suggesting that it is better representative of effort, whereas other authors have considered it synonymous with load. Fisher and Smith are not the first to suggest that the use of intensity to refer to load in RT is inappropriate. Others have previously attempted to instigate a change in the language used by researchers and practitioners. Despite previously finding myself supporting this view (that intensity is better defined as effort and not load) regarding the use of the term and having published as such, further consideration has left me doubting the value of both interpretation of intensity as synonymous with load or effort. Thus, this editorial seeks to ask the readers of BJSM, and the wider community involved in RT, to consider the use of the term intensity as it stands and whether both sides of the disagreement are defending inappropriate idioms. More specifically, however, it asks, `Is it time to drop the term altogether?`